Kinetic and Equilibrium Studies on the Adsorption of Pb(II), Cd(II) and Cu(II) by Rape Straw - Xiao-Bao Gong (Adsorption Science & Technology)
Various kinds of biological materials have been investigated as an alternative biosorbent to treat low-metal-bearing wastewaters. In this study, rape straw (RS), a kind of agricultural waste abundantly available at no cost, was used as an efficient biosorbent for the removal of Pb(II), Cd(II) and Cu(II) ions from aqueous solutions. The maximum adsorption capacity of RS was found to be 61.9 mg g −1 for Pb(II) at pH 4.0, 17.7 mg g −1 for Cd(II) at pH 6.0 and 7.82 mg g −1 for Cu(II) at pH 5.0. The Langmuir isotherm model provides the closest fit to the adsorption data of Pb(II) and Cd(II), whereas the Freundlich model best explained the adsorption of Cu(II). Moreover, the adsorption data of these three metals were all well fitted by the pseudo-second-order kinetic model. Scanning electron microscopic analysis demonstrated a conspicuous surface morphology change in the Pb(II)-, Cd(II)- or Cu(II)-adsorbed adsorbent system. Results of Fourier transform infrared spectrum analysis suggested the involvement of amine, carboxyl, phosphate and hydroxyl groups during adsorption. Based on the study results, it can be concluded that RS can be evaluated as an alternative biosorbent to remove Pb(II), Cd(II) and Cu(II) ions from industrial wastewaters.